ANALISIS PERAN DUKUNGAN SOSIAL DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MAHASISWA - Rauhul Khotimah; Nurus Sa'adah (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2023)
This study aims to examine the role of social support in increasing student motivation tolearn. This research is a literature study where the researcher conducts an in-depth study ofprevious research. Students have a role as a learner and interact with other students.Positive social support possessed by students can help students face their learning demandsand can be a generator of learning motivation, with motivation to improve learning order,learning independence, acceptance and social presence, critical thinking skills, writingskills, problem solving abilities, and of course can support learning achievement. Thepurpose of this study will be to examine the relationship between social support andlearning motivation, namely a description of learning motivation with sources of socialsupport that influence each other. The type of research used is a study (literature review),where the authors seek references from significant journal articles with cases or problemsthat have been determined. Collecting data in this study by searching for literature, bothjournals and articles relevant to the title under study, literature searches were carried outfrom several search pages, websites such as Scientific Direct, Proquest, Scholar, GarudaPortal, Research Gate, and other sites.Keywords: Social Support; College student; Motivation to learn